Searching for seadragons: predicting micro‐habitat use for the common (weedy) seadragon (Phyllopteryx taeniolatus) based on habitat and prey. Issue 4 (13th March 2022) - Allan, Sam J.; O'Connell, Max J.; Harasti, David; Klanten, O. Selma; Booth, David J.
Abstract: Habitat associations can be critical predictors of larger‐scale organism distributions and range shifts. Here the authors consider how a critical habitat, kelp ( Ecklonia radiata ) and prey (mysid crustacean swarms), can influence small‐ and large‐scale distribution on the iconic common (weedy) seadragon ( Phyllopteryx taeniolatus :Syngnathidae). P. taeniolatus are charismatic fish endemic to the temperate reefs of southern Australia, reported to range from Geraldton, Western Australia (28.7667°S, 114.6167°E) around southern Australia to Port Stephens, New South Wales (32.614369°S, 152.325676°E). The authors test a previously developed model of seadragon habitat preferences to predict P. taeniolatus occurrence within four sites from Sydney to the northern limit of their range in eastern Australia. They determined that P. taeniolatus associations with Ecklonia and mysid shrimp can be extrapolated across multiple sites to predict the occurrence of individual P. taeniolatus within a location/site. For instance, the authors demonstrated a significant positive relationship between the density of mysid swarms and the density of P. taeniolatus, evident across all sites despite large differences in the density of mysid swarms among sites. The findings are the first to model P. taeniolatus habitat associations across multiple sites to the northern limit of their range and have applications in protecting P. taeniolatus populations and how they may respond under climate change scenarios, such as poleward kelp retractions.